2022
DOI: 10.1159/000521713
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Early Additional Hemoperfusion Therapy for Severe COVID-19 Patients: A Prospective Cohort Study

Abstract: <b><i>Introduction:</i></b> Currently, the effect of hemoperfusion on outcome in severe COVID-19 patients is still unknown. Therefore, we aimed to investigate the effects of early HA-330 hemoperfusion in severe COVID-19 patients. <b><i>Methods:</i></b> We conducted a single center, prospective cohort study on patients who were diagnosed with severe COVID-19 patients and admitted to ICU. Patients in hemoperfusion group (defined as patients who were treated with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…It means that early initiation of hemoadsorption can be extremely effective in patients with severe COVID-19. Surasit et al [ 62 ] conducted a prospective cohort study to compare 2 groups: patients with standard therapy and patients who received at least 3 hemoadsorption procedures using an HA 330 (Jafron Biomedical Co., China). The result of this study was that in the group of patients who had the hemoadsorption procedure, there was a marked improvement in laboratory parameters, and the 28-day mortality rate was significantly lower in the hemoperfusion group compared to the control group (6.67% vs 85.71%, p < 0.001).…”
Section: Hemoadsorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…It means that early initiation of hemoadsorption can be extremely effective in patients with severe COVID-19. Surasit et al [ 62 ] conducted a prospective cohort study to compare 2 groups: patients with standard therapy and patients who received at least 3 hemoadsorption procedures using an HA 330 (Jafron Biomedical Co., China). The result of this study was that in the group of patients who had the hemoadsorption procedure, there was a marked improvement in laboratory parameters, and the 28-day mortality rate was significantly lower in the hemoperfusion group compared to the control group (6.67% vs 85.71%, p < 0.001).…”
Section: Hemoadsorptionmentioning
confidence: 99%
“…Trials 21(1):577 10.1186/s13063-020-04,501-0 HA 330 (Jafron, Biomedical Co, China) Due to the macroporous structure and high specific surface area removes target molecules from the bloodstream [ 11 ]. Two comparative studies demonstrated a decrease in the pateints’ mortality, compared with the control group [ 51 , 62 ] When used in the early stages of the disease may have a beneficial effect on improving the patient's condition and decreasing mortality [ 62 ] Yang X–H, Ren-Hua S, Ming-Yan Z, Er-Zhen C, Jiao L, Hong-Liang W, Rong-Li Y, De-Chang C (2020) Expert recommendations on blood purification treatment protocol for patients with severe COVID-19. Chronic Diseases and Translational Medicine 2/9 10.1016/j.cdtm.2020.04.002 Surasit K, Srisawat N (2022) The Efficacy of Early Additional Hemoperfusion Therapy for Severe COVID-19 Patients: A Prospective Cohort Study.…”
Section: Selective Plasma Filtrationmentioning
confidence: 99%
See 2 more Smart Citations
“…HA330 showed favorable outcomes in acute respiratory distress syndrome in terms of oxygenation, reduction of lung edema, and circulating and alveolar cytokine levels in patients with sepsis shock and acute respiratory distress syndrome (ARDS) [ 98 ]. Specifically, in patients with COVID-19, a single-center prospective cohort study demonstrated that the early use of HA-330 hemoperfusion in addition to standard therapy improves organ failure outcomes (SOFA score, mechanical ventilator-free day) and may indirectly reduce the mortality rate [ 99 ]. The limited sample size of this study and the lack of confirmation studies in COVID-19 patients complicate the interpretation of these results.…”
Section: Role Of Dialysis In the Treatment Of Patients With Covid-19 ...mentioning
confidence: 99%